TREND PARIWISATA HALAL INDONESIA DALAM PERSPEKTIF ISLAM - Sismanto, Sismanto (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
This article is based on a critical assessment of various literature to find concepts and discuss trends in halal tourism in Indonesia. The authors find several references, documents, and other relevant data derived from previous studies and personal observations to provide insight into the subject under study. The findings reveal that: (1) Halal tourism in an Islamic perspective is contained in QS. Ali Imran: 137, QS. Ar Ruum: 42, QS. An Nahl: 36, QS. Al An'am:11, QS. Al-Ankabut: 20, QS. Al An'am:11, QS. As Saba':11 and reinforced by the hadith, (2) Indonesia occupies the top position in the world in terms of communication and services. It is not included in the top ten in terms of access and environment. The regions of Lombok, Aceh, and Riau are in Indonesia's top three halal tourism destinations.